Alternative Transcription at Venom Genes and Its Role as a Complementary Mechanism for the Generation of Venom Complexity in the Common House Spider - Haney, Robert A.; Matte, Taylor; Forsyth, FitzAnthony S.; Garb, Jessica E. (Frontiers in Ecology and Evolution, 2019)
The complex composition of venom, a proteinaceous secretion used by diverse animal groups for predation or defense, is typically viewed as being driven by gene duplication in conjunction with positive selection, leading to large families of diversified toxins with selective venom gland expression. Yet, the production of alternative transcripts at venom genes is often overlooked as another potentially important process that could contribute proteins to venom, and requires comprehensive datasets integrating genome and transcriptome sequencing together with proteomic characterization of venom to fully document. In the common house spider, Parasteatoda tepidariorum, we used RNA sequencing of four tissue types in conjunction with the sequenced genome to provide a comprehensive transcriptome annotation. We also used mass spectrometry to identify a minimum of 99 distinct proteins in P. tepidariorum venom, including at least 33 latrotoxins, pore-forming neurotoxins shared with the confamilial black widow. We find that venom proteins are much more likely to come from multiple transcript genes, whose transcripts produce distinct protein sequences. The presence of multiple distinct proteins in venom from transcripts at individual genes was confirmed for eight loci by mass spectrometry, and is possible at 21 others. Alternative transcripts from the same gene, whether encoding or not encoding a protein found in venom, showed a range of expression patterns, but were not necessarily restricted to the venom gland. However, approximately half of venom protein encoding transcripts were among the 1318 transcripts with strongly venom gland biased expression. Our findings reveal an important role for alternative transcription in generating venom protein complexity and expand the traditional model of venom evolution.